1979
DOI: 10.1212/wnl.29.8.1084
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography and childhood seizure disorders

Abstract: Computerized tomography (CT) was performed on 256 children with seizure disorders. The incidence of abnormal scans was closely related to seizure type, and permitted separation of patients into a low-yield and a high-yield group. Low-yield groups included children with idiopathic generalized seizures, children in whom both the neurologic examination and electroencephalogram (EEG) were normal, and children with a generalized seizure of unknown etiology in whom the neurologic examination and the EEG were normal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 0 publications
1
33
1
Order By: Relevance
“…20,21 Extrapolation of data from the literature on the use of CT in neurologically healthy children who have generalized epilepsy has shown that clinically important intracranial structural abnormalities in this patient population are uncommon. 22,23 …”
Section: Action Statementmentioning
confidence: 99%
“…20,21 Extrapolation of data from the literature on the use of CT in neurologically healthy children who have generalized epilepsy has shown that clinically important intracranial structural abnormalities in this patient population are uncommon. 22,23 …”
Section: Action Statementmentioning
confidence: 99%
“…48 In the Class I study in which 19 CT scans were done in selective cases (first seizures if greater than age 6 years, head trauma, or focal seizure), there was one significant abnormality (age of the patient was not given), a subdural hematoma, not predicted by history and physical examination. 14 Of the 14 Class II studies, nine involved children only (n = 2559), 17,19,[49][50][51][52][53][54][55][56] four were of adults only (n = 666), 24,42,57,58 and one involved children and adults (n = 109). 59 Only a small percentage of children in these studies (0 to 7%) had lesions on CT that altered or influenced management.…”
Section: Recommendationsmentioning
confidence: 99%
“…The yield of abnormality on CT when the neurologic examination and EEG were normal was 5 to 10%. 50,54 In a Class II study in which seven children (14% of children with nonfebrile seizures) had CT scans that influenced management, five had focal or complex partial seizures. Abnormalities on neuroimaging were associated with a higher recurrence risk.…”
Section: Recommendationsmentioning
confidence: 99%
“…In a study conducted by Yang P et al, 17 out of 34 children with partial seiZlil';S had an abnormal cr. the commonest being atrophy [14]. Five cases had focal calcification [Fig 3) on cr of which two had a history of having been treated for tuberculosis and in one there were multiple calcification suggestive of healed granulomas.…”
Section: Discussionmentioning
confidence: 99%